Immunogenicity and safety of measles-mumps-rubella vaccine delivered by the aerosol, intradermal and intramuscular routes in previously vaccinated young adults: a randomized controlled trial protocol - Sumanta Saha; Melanie Millier; Ari Samaranayaka; Liza Edmonds; Emma Best; James Ussher; Andrew Anglemyer; Jennifer Lee; Michael Tatley; Felicity Cutts; Rob van Binnendijk; Peter McIntyre (PLoS ONE, 2025)
Background There are increasing reports of outbreaks of measles in countries that achieved measles elimination using two doses of measles-mumps-rubella (MMR) vaccine, particularly in health care settings. While responses to a third dose of MMR in two-dose recipients have been examined, these studies have all administered MMR by the standard (intramuscular or subcutaneous) route, and data on the duration of antibody are limited. We have developed a protocol for an open-label parallel-arm randomized-controlled trial to compare measles antibody responses and safety after intradermal and aerosol administration of MMR with intramuscular, the usual mode of administration in Aotearoa (New Zealand). Methods Eligible participants are aged ≥ 18 years who have previously received two doses of the MMR vaccine and based on levels of IgG antibody to measles or mumps below the threshold for seropositivity in commercially available screening tests are required to receive the MMR vaccine prior to entering health professional training programs at Aotearoa universities. The participants will be randomized to three routes of administration (1:1:1) to receive the MMR vaccine by the intradermal (via microneedle), intrapulmonary (via vibrating mesh nebulizer), or intramuscular routes. The primary objective is to determine the proportion of participants who attain levels of measles IgG antibody above the seroprotective threshold using a multiplex bead-based immunoassay, with those in the lowest quartile validated by plaque neutralization assay, at days 6–8, 13–15, 28–42, and at 12–18 months post-vaccination. Secondary objectives include a fold increase in the geometric mean concentration of IgG antibody from baseline, and systemic and local reactions following delivery of MMR by each method. The trial is registered with the Australian New Zealand Clinical Trials Registry (ANZCTR; https://www.anzctr.org.au/Default.aspx; trial registration no. ACTRN12623000130662).